Science and Geopolitics of The White World Arctic-Antarctic-Himalaya (Springer International Publishing, 2018)
This book brings together thirteen selected papers presented in the Third International Seminar on Science and Geopolitics of Arctic-Antarctic-Himalaya, held in India in September 2015. The papers and have been grouped according to the Seminar's three main themes: a) Geopolitics of the Polar Regions, b) Global Climate Change and Polar Regions, and c) Climate Change and Himalayan Region.